DIAGNÓSTICO SOBRE O USO DE FERRAMENTAS DE TECNOLOGIA DA INFORMAÇÃO NA GESTÃO DA RESPONSABILIDADE SOCIAL. - Machado, Marcelo Corrêa (2013)
The growing standardization activities in all sectors of the contemporary society shapes business management as the new standards, or revisions of the already issued standards, begin to move from the initial level of certifications related to quality assurance or environment, or the safety and health at work, and advance into management issues such as risk and social responsibility, getting strategic focus and providing competitive advantage for organizations that adopt them. The implementation of the management of these aspects through its specific standards or management systems in an integrated manner and through computer systems, as well as the understanding of the effects and impacts of these new management systems within organizations still represent a major challenge. Understanding this new scenario will allow organizations to exploit such management systems and their applications in their processes, achieving improvements not only in the direct results of their activities, but in all spheres of the activities from the organization. In this sense, this research seeks to analyse through an applied research, exploratory and descriptive, by reviewing literature and documents and, with the aid of a field study of multiple cases, how the use of IT is being applied in the management of social responsibility, as well as the impact to implement management tools among companies, especially for the Brazilian standard of social responsibility management, ABNT NBR 16001:2012. It was concluded that the use of IT in social responsibility management field is still unexplored by certified companies due to the low use of IT solutions both in the implementation and management of social responsibility, and demonstrating that future research may also contribute to this field.